EDUKASI DAN DETEKSI DINI GEJALA DIABETES MELITUS TIPE 2 SEBAGAI UPAYA PENINGKATAN KESADARAN KESEHATAN MASYARAKAT DI PUSKESMAS PLAOSAN, MAGETAN - Murti, Bhisma; Susiani, Ely Tri; Nur Syahbani, Andi Syahrani; Kurniawan, Ilham Raka; Sujatmiko, Ramdhani; de Souza, Jeronimo (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
Type 2 Diabetes Mellitus is one of the non-communicable diseases whose prevalence continues to increase and is often undetected in the early stages. Low public awareness of risk factors and early symptoms is a serious challenge for prevention efforts. This service activity aims to increase public knowledge and awareness about the early symptoms of Type 2 Diabetes Mellitus through health education and early detection. This study aims to determine the role of Education and Early Detection of Type 2 Diabetes Mellitus Symptoms as an Effort to Increase Public Health Awareness at the Plaosan District Health Center, Magetan Regency. The method used is the ABCD (Asset-Based Community-driven Development) approach which emphasizes the use of community potential as the main capital in promotive and preventive efforts. The activity was carried out at the Plaosan Health Center, Magetan by involving the community as an audience, providing interactive education and simple examinations as a form of behavior change, under the condition of limited access to adequate health information, with a target degree of increasing public understanding of at least 75% of the initial symptoms of diabetes and the willingness to carry out routine checkups. The results of the activity showed a significant increase in public knowledge, as seen from the increase in the number of participants who were able to mention the early symptoms of Type 2 Diabetes Mellitus and the increasing interest in conducting periodic blood sugar level checks. The results of the statistical test showed a significant difference between the pretest and posttest scores (Z = -5.292; p = 0.000), which indicates that education based on the CERDIK approach (Periodic Health Checks, Quitting Cigarette Smoke, Being Physically Active, Eating a Balanced Diet, Getting Enough Rest, and Managing Stress) is effective in increasing public health literacy about diabetes prevention. Thus, the ABCD approach is effectively used in increasing public health awareness, especially in the prevention and early detection of Type 2 Diabetes Mellitus.